Design and Construction of Bamboo Products and Rattan Accessories by the Local Artisans of Lahore Pakistan - Kashif, Javed (International Journal of Humanity and Social Sciences, 2024)
Purpose: Bamboo and rattan are two materials that greatly affect all products, fixtures, and items designed and made by artisans in Lahore, Pakistan. The aims of this research encompass the study of the traditional and contemporary practices of design and the construction methodologies adopted by the people in the area regarding the formation of basic bamboo products and rattan accessories significantly basketry manufacture in Lahore. Coming from a backdrop of knowledge transfer within families, global resources and design trends, strong vectors for sustainability, minimalism, functionality, significant development in technique and aesthetics was taken up for analysis in the study. Further, it will discuss the economic stature of local artisans amidst the economic challenges. Methodology: For this purpose, a comprehensive research has been conducted into the bamboo and rattan market in Lahore, Pakistan. The study documented insights from the interviews with local artisans specializing in bamboo and rattan craftsmanship and all their observations. The research has gathered rich first-hand data on design practices, material uses and infusion of modern influence in their work, as it engaged actively with the craftspeople. Findings: The handicraft industry of bamboo and rattan in Lahore is feeling both challenges and opportunities. The industry had then begun to bear strained supplies, with growing costs towards the case of Pakistan's timber industry. Reduced spending by consumers has turned out to disrupt the supply line and eventually the livelihoods of those artisans, since rising material costs and government taxing were on the rise. It is strategic adaptations that will help the industry to prosper with government support and sustainable practice. Unique Contribution to Theory, Policy and Practice: This study presented a number of recommendations for creating an awareness, developing frameworks, improving practices, and encouraging authorities to take major actions in order to support bamboo and rattan artisans in Lahore, Pakistan. It could be focusing on historic handcrafts, modern design concepts and construction techniques. Hence, through this process, the art of producing accessories will be revived, thereby harnessing the economic feasibility of the products and accessories industry of Pakistan.